(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article intends to reflect on the processes of patrimo- nial appropriation of traumatic memories which are being constructed through state and civil initiatives within the fra- mework of certain public policies of memory that the gover- nments of the Southern Cone of Latin America have been driving. In this environment, the museums of the report have been set up as promoters of human rights in tandem with the process of rebuilding the memory linked to recent dic- tatorships. As these are museums that operate with painful memories that not every society recognizes, they are spaces of conflict. However, a process of patrimonial appropriation of painful memories can be seen in these proposals, to the extent that they establish, promote and expand their scope and mission to raise awareness and educate in the societies in which they are installed.